Experimental Investigations on Shakedown of Portal Frames - M.H. Ali; J.A. Konig; O. Mahrenholtz (Engineering Transactions, 1984)
The paper presents results obtained in tests consisting of cycling loading of a two-span continuous beam as wall as of some portal frames made of mild steel. The investigations were performed for various load intensities so as to determine the maximum intensity at which the defections stabilization still takes place, i.e. a given structure shakes. down. The results a.re in a fair agreement with the predictions of the shakedown theory and thus confirm its practical applicability in the design of steel structures.